Demographic processes in the Armenian and Azerbaijani communities of the North Caucasus in 1991-2022. (using the example of Stavropol Territory) - Badalyan, Irina (History and Culture, 2025)
The study of the Armenian and Azerbaijani communities formed in different parts of the North Caucasus has been highly important in recent decades. During the study, we observed the demographic picture of the Armenian and Azerbaijani communities of the Stavropol region, studied and analyzed the existing problems, as well as researched the demographic processes and trends. Comparisons and analyzes of the movements, processes, and realities of the two communities will be highlighted. The main task of the topic is to study the reasons for the formation of communities, the distribution of Armenian and Azerbaijani communities in the Stavropol region, the dynamics of the growth or decline of communities, factors affecting emigration from Armenia and Azerbaijan, inter-ethnic ties, business relations, educational and cultural exchanges. The study showed that the demographic processes of Armenians and Azerbaijanis in the Stavropol region of the North Caucasus were shaped by historical events, including conflicts, migrations and political changes. The Nagorno Karabakh conflict between Armenia and Azerbaijan has led to displacement in both communities. Armenians in Azerbaijan and Azerbaijanis in Armenia have been forced to flee their homes due to violence and ethnic tensions, with some seeking refuge in the North Caucasus and other regions
Keywords: North Caucasus; Stavropol region; demography; armenians; azerbaijanis; diaspora; migration